From garden to kitchen - Mohd Shukri, Nor Azwani (Department of Nutrition Sciences, 2022)
Ulam is a Malay word referring to parts of plants that can be eaten raw or with minimal processing, like blanching, steaming, or boiling. Deliciously eaten with sambal, these ulam can also be used as ingredients in many delectable dishes. Taking ulam into another level to make it more appetizing and appealing is what the ‘from Garden to Kitchen’ recipe e-book is all about.